Indonesia : Tenth Review Under the Extended Arrangement and Request for Waiver of Applicability. (IMF Staff Country Reports; Country Report, 2003)
Macroeconomic performance has evolved in line with program projections, and financial market sentiment remains strong. Although the political situation remains stable, electoral politics are expected to intensify in advance of next year's general elections. The authorities indicated that they were committed to ensuring a successful completion of the program, and to developing a credible and comprehensive policy framework for next year. The authorities also noted that progress had been made more generally in strengthening the governance of the state banks.